The Effect of Creating a Sense of Individual and Collective Psychological Ownership of the Brand in Online Communities on Buying Behavior and Online Word-of-Mouth Advertising - Yazdan Shirmohammadi; Jahan Rajabi (مدیریت نوآوری و راهبردهای عملیاتی)
Purpose: This study aims to investigate the effect of creating individual and collective psychological ownership of the brand for customers on buying from the brand and word-of-mouth advertising through partnership goals with a modifying role of members' activities in Mahan Airlines as a case study.Methodology: This research is an applied and descriptive survey regarding purpose and method. The sampling method of this study was random, and its number was 384 people. The assessment tool in this study was a researcher-made questionnaire. Statistical analyses were performed using structural equation methods and SPSS and Smart-PLS2 software programs. We used a structural equation modelling method to determine the causal relationship between the variables.Findings: The results showed that self-efficacy, responsibility, belonging, personal identity, and collective psychological ownership positively and significantly affect members' participation goals. Also, the partnership's goals positively and significantly affect the purpose and intention of buying the brand and word-of-mouth advertising.Originality/Value: The study showed that self-efficacy, responsibility, belonging, personal identity, and collective psychological ownership have a positive and significant effect on the goals of participation and by modifying the type of activity of members.